The Relationship between Public Knowledge About Fluorine and Prevention of Dental Caries in Kandang Village, Darul Imarah District, Aceh Besar District - Cut Ratna Keumala; Ratna Wilis (Science Midwifery, 2022)
Dental caries is an infectious and multifactorial disease that affects some people. A simple and economical procedure can prevent caries by brushing the teeth with fluoride toothpaste. Using fluoride toothpaste is thought to reduce the incidence of dental caries. However, knowledge about fluoride in reducing dental caries is still limited among the community, so the status of dental caries is still high. Therefore, a study is needed to determine the relationship between public knowledge about fluoride and the prevention of dental caries in Kandang Village, Darul Imarah District, and Aceh Besar District. This study used a cross-sectional approach located in Kandang Village, Darul Imarah District, and Aceh Besar District. The research will be conducted on March 11-17. The population in the study was the entire community in Kandang Village, Darul Imarah District, and Aceh Besar District. Sampling in this study amounted to 68 people using the Slovin formula. Data analysis used univariate and bivariate analysis. The results showed a relationship between public knowledge about fluoride and the prevention of dental caries in the people of Kandang Village, Darul Imarah District, Aceh Besar District, as evidenced by the results of statistical tests with a P value of 0.002 < 0.05. Public knowledge about fluoride was mainly in the low category. Fifty respondents (73.5%), and the dental caries status of the people of Kandang Village was mainly in the high category, namely 23 respondents (33.8%).